What Works to Improve Staff Compliance With Multi-Drug-Resistant Organism (MDRO) Screening - Hernandez MA (Sigma Theta Tau International Honor Society of Nursing)
What Works to Improve Staff Compliance with Multi-drug Resistant Organism (MDRO) Screening Monina H. Gesmundo, MN (Honours), PGDip HSc (Merit), PGCert Tertiary Teaching, BSN, RN, RM, CNS School of Nursing, Massey University, Auckland, New Zealand Purpose of the presentation: To present the evaluation of the effect of multi-modal interventions on the staff MDRO admission screening compliance rate in various departments of a tertiary public hospital in New Zealand Target Audience: The target audience of this presentation are staff nurses, nurse educators, nurse managers, quality improvement advisers and infection control practitioners who are keen to identify interventions that work in improving staff compliance to MDRO admission screening Objective: To evaluate the effect of multi-modal interventions on the staff MDRO admission screening compliance rate in various departments of a tertiary public hospital Research question: What is the effect of multi-modal infection prevention and control interventions on the staff MDRO admission screening compliance rate in various departments of a tertiary public hospital? Design: A retrospective review of monthly MDRO admission screening audits was done to compare the compliance rate before and after multi-modal interventions were implemented. The audit was conducted in the care of older people and elective surgical department of a public tertiary hospital in Auckland, New Zealand from December 2010 to November 2014. Setting: Two departments of a public tertiary hospital in Auckland, New Zealand Methods: Monthly MDRO admission screen audits were done in a representative ward of each department for the purpose of quality improvement. Audits were conducted by generating a monthly list of patients who were eligible to be screened for MDRO on admission to the ward. Twenty patients were randomly selected from the monhtly list for a specified period of time to evaluate whether nurses screened them for MDRO within 24 hours of admission. Eligibility to be screened is based on the criteria published in the organisational policy for MDRO management. Nursing staff compliance rate with the MDRO admission screen policy was computed using frequency and percentage. Multi-modal interventions focusing on the nursing staff were implemented by the infection control practitioner. Interventions include: monthly MDRO admission screen compliance audits, regular reporting of audit result, feedback with regard to missed screens, regular education sessions with the nursing staff and staff encouragement from both the infection control practitioner and nurse manager. Compliance rates were reported to the charge nurse managers on a monthly basis through an e-mail. Compliance rates of greater than 90% were celebrated and reinforced, whereas a drop in the compliance rate or a compliance rate of < 90% was followed up with the nurse manager. Regular 10-15 minute-education sessions during staff handovers were done by the infection control practitioner to present the audit results, to provide input, to answer queries and to encourage the staff to do better. Nurse managers also encourage staff to improve screening compliance rate. Data analysis utilized Microsoft Excel Software in quantitative data collation and encoding. MDRO admission screen audits were presented using descriptive statistics such as frequency, percentage, mean, median and mode. Standard deviation was used to show data variability. T-test was utilized to test for a significant difference in the overall compliance rate before and after the multi-modal interventions were introduced. T-test is a parametric procedure of testing the difference in group means. The level of significance was set at P < 0.05 to identify a significant difference in the compliance rate. Results: Results show that the MDRO admission screen compliance rate in the two departments were variable. The average compliance rate from October, 2012 to November, 2014 in the elective surgical department is 85.75% compared to 75.91% from December, 2010 to September, 2012 (Table 1). Table 1.MDRO admission screen compliance at the elective surgical department Surgical Department Before* After** Mean 75.90909091 Mean 85.75 Number of patient records audited 1670 Number of patient records audited 2058 Number of monthly audits completed 22 Number of monthly audits completed 24 *Period coverage is from December, 2010 to September, 2012 **Period coverage is from October, 2012 to November, 2014 In the care of older people department, results show that the MDRO admission screen compliance was also variable. The average MDRO admission screen compliance rate from August, 2013 to October, 2014 is 96.80% compared to 83.84% from December, 2010 to July 2013 (Table 2). Variability in the compliance may be due to patient acuity, staff mix, thorough history-taking of the patient, review of previous admissions, completeness of handover, staff knowledge of the organisational policy, staff motivation to adhere to organisational policy and availability of staff support. Table 2.MDRO admission screen compliance at the health of older people department Health of Older People Before*** After**** Mean 83.83870968 Mean 96.8 Number of patient records audited 2599 Number of patient records audited 1452 Number of monthly audits completed 31 Number of monthly audits completed 15 *** Period coverage is from December, 2010 to July 2013 ****Period coverage is from August, 2013 to October, 2014 Statistical analysis of the overall MDRO admission screening compliance rate before and after the interventions showed a significant difference (P < 0.05) in the compliance rate in both departments. A two-sample T-test with unequal variance was utilized in the statistical analysis given the variability in the screening rate and count. Table 3 provides a summary of the statistical testing done. The last column shows that there is a significant difference in the compliance rate in the surgical department (P < 0.009) and the care of older people department (P < 0.00003) Table 3.Descriptive summary of statistical testing of the MDRO admission screen compliance rate before and after the interventions Departments Before After T-Test (P < 0.05) Number of Audits Mean Compliance Rate Number of Audits Mean Compliance Rate Surgical Department 22 75.91 24 85.75 0.009324379 Care of Older People 31 83.84 15 96.80 0.000036141 Conclusion: The multi-modal interventions addressed to nurses had a significant impact on the MDRO admission screening compliance rate in various departments of a tertiary public hospital. While various factors may affect the staff MDRO admission screening compliance rate, the rate could be kept at a high level through regular audits, regular reporting of audit result, regular education sessions and consistent staff encouragement.
Keywords: MDRO Admission Screen; Multi-modal Interventions; Nursing Staff Screening Compliance